A letter to the Lord Chief Justice Campbell : containing remarks upon the conduct of the prosecution and the judges, with strictures on the charge delivered to the jury, illustrative of its dangerous tendencies to the long-enjoyed rights and privileges of Englishmen - Palmer, Thomas, b. 1828; Campbell, John Campbell, Baron, 1779-1861 (British trials, 1660-1900, 1856)
Attack on his conduct in the trial of William Palmer for the murder of John Parsons Cook.